A clinicopathological study of patients with sino nasal polyposis in tertiary care centre - Gowda, Belure Gowda Paduvalahippe Raje; Vishwanath, Vinay Kumar Mahadikar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Masses in sino nasal cavity presents with wide range of complaints like nasal obstruction, nasal discharge, epistaxis, headache, swelling in and around the nose, through clinical examination, rigid nasal endoscopy and by use of advanced imaging technique computerized tomography (CT), magnetic resonance imaging (MRI) of nose and paranasal sinuses. Presumptive diagnosis is often made. However, it is a careful histopathological examination which divides the nature of any particular lesion, like neoplastic benign or malignant or non-neoplastic and inflammatory which makes possible to implement correct and timely intervention, which is a major dividing factor for better prognosis. Methods: A total of 100 cases of nasal polyps were studied by the department of ENT at Hassan institute of medical sciences, Hassan during a period of 1 year from January 2019 to January 2020. They were treated surgically by endoscopic excision, lateral rhinotomy or by radical surgery. All the excised masses were sent for histopathological examination to determine their final diagnosis. Results: The middle age group of 21 to 30 years was the most common age group affected with more male predominance. Nearly 85% of the cases were non-neoplastic. The most common presentation was nasal obstruction with ethmoidal sinus being the commonest sinuses seen in the present study. Conclusions: Polypoid lesions in the nasal cavity and paranasal sinuses may range widely from benign to malignant affecting all the ages. Common nasal lesions were seen in age group 21-30 years and maximum lesions were non- neoplastic.